Bernard Shaw's Henry Higgins: A Classic Aspergen. - Weintraub, Rodelle (English Literature in Transition, 1880-1920, 2006)
This article focuses on the character Henry Higgins in Bernard Shaw's theatrical production "Pygmalion." The playwright described the character as a middle-aged bully who was indifferent to young women. Jackie Maxwell has unintentionally directed Higgins as an adult Asperger in her Shaw Festival Theatre production in 2004. An individual who has Asperger's Syndrome has difficulties in social interaction and lacks empathy.